Analysis Implementation Taxation Liability of Income Article 4 Paragraph (2) on Land and/or Building Rent Activities at PT. Pegadaian Kanwil V Manado - Meicelin Omega Joevanda Tangka; Novi S. Budiarso; Christian V. Datu (Jurnal Ekonomi dan Bisnis Digital, 2023)
Tax is one of the biggest sources of state revenue. PPh Article 4 Paragraph (2) is a type of income tax in Indonesia. The tax object of PPh Article 4 paragraph (2) is from land and/or building rental activities. This study aims to find out how the implementation of tax obligations regarding the calculation of rates, deductions, deposits, and reporting of Article 4 Paragraph (2) PPh on land and/or building rental activities at PT Pegadaian Kanwil V Manado. The method used in this study is a qualitative descriptive analysis method, where observations and interviews are carried out. Based on the results of existing research, it can be seen that PT Pegadaian Kanwil V Manado has carried out its tax obligations, namely calculating, deducting, depositing, and reporting PPh Article 4 Paragraph (2). The implementation of its obligations has been carried out in accordance with the applicable tax regulations and has followed the development of the latest tax regulations and has implemented them.